Current Mode Full Wave Rectifier Topology for Integration - Ansari Faheem, Shahzad Mobeen, Siddiqui Mohsin, Ashfaque Ahmed, Fahad Bilal (International Journal of Advanced Science and Technology, 2020)
A current mode full wave rectifier is presented. Only six transistors are used making in this circuit. The assembly of cmos is simulated using Cadence Virtuoso simulation software with its default gpdk180 model, i.e. 180nm technology. Layout of the design is also presented for integration of the circuit in IC form. Rectifier is accurate and precision for low current signals, and for currents with high value its W/L ratio can be adjusted to get the desired output. Frequency range of the rectifier is between lowest frequency to upto 20MHz, and can also be extended by minute changes in W/L ratio. Key Words:gpdk180 model, Cadence Virtuoso